Banana leaf in the diet of laying hens in cage free system - Nayara Emanuelle Matos e Silva; Heder José D'Ávila Lima; Jean kaique Valentim; Fernandes Jesuino Mukissaí Tossué; Tatiana Marques Bittencourt; Jonatan Mikhail Del Solar Velarde (Acta Scientiarum. Animal Sciences, 2019)
The aim of this research was evaluate the productive performance, egg quality and the endoparasites presence on Carijo laying hens in Cage Free system, fed with two experimental diets, one of them supplemented with fresh banana leaf in natura. Were used 196 laying hens with twenty-four weeks of age, distributed in a completely randomized design with 14 boxes, two experimental diets and seven replicates, by treatment with fourteen birds per experimental unit. The variables analyzed were: feed intake; egg production; egg mass: feed conversion per egg mass; feed conversion per dozen eggs; egg weight; albumen weight; yolk weight; shell weight; yolk percentage; albumen percentage shell percentage; yolk pigmentation and the presence of endoparasites. No influence (p > 0.05) were found, for performance and egg production, in Carijo laying hens fed supplemented with banana leaf in natura. For the treatment with inclusion of banana leaf, yolk pigmentation were superior (p < 0.05) when compared to control diet, producing eggs with more yolks orange color. In respect to endoparasite analysis, there was significant effect (p < 0.05) in the percentage of infections present in excretas. Among the treatments evaluated, the one with banana leaf supplementation reduced in 26.54% the endoparasites presence. The inclusion of banana leaf in the diet of Carijo laying hens does not affect performance and eggs quality and decreases the amount of endoparasites of the genus Strogyloides spp.